Interpretation and Use of Generator Reactive Capability Diagrams - Jackson, J. Y. (IEEE transactions on industry and general applications, 1971)
The operating characteristics of generators are discussed with particular emphasis on those used in the generation of power for industry. Methods of operation of generators within safe limits are presented and related to a reactive capability curve.